Supplemental data acquisition tools for modeling environmental systems - Steidley, Carl W. (2005)
The goal of our on-going research is to develop effective and reliable tools for modeling the environmental systems of the Gulf of Mexico. For example, our on-going research into methodologies for the prediction of water levels in the shallow waters of the bays and estuaries along the Texas Gulf coast. Our modeling approaches are based on the real-time data collected by the Texas Coastal Ocean Observation Network(TCOON). TCOON is managed by the Division of Nearshore Research (DNR) in cooperation with the Department of Computing and Mathematical Sciences (CAMS) both of Texas A& M University-Corpus Christi. TCOON consists of approximately 50 data gathering stations located along the Texas Gulf coast from the Louisiana to Mexico borders. In addition to a short description of our major data acquisition system for our research efforts, this paper presents design issues, development issues, and test results encountered in the production of two supplemental data acquisition systems as well as several of our environmental systems modeling efforts at Texas A&M University Corpus Christi.